A new paradigm in PhD education: mapping and integrating psychosocial competencies to the PhD curriculum - Diane A. Safer; Victoria H. Freedman; Arther B. Markman (Frontiers in Education)
The development of a PhD student into a professional requires intellectual, technical, and psychosocial competencies. Ten proposed core competencies are considered essential for equipping PhDs with the skills needed to succeed in the future, no matter which field or career path they choose. Half of these involve technical competencies, which can be developed through classes, from hands-on experiential learning, and with guidance from mentors. The remaining half involve psychosocial competencies, which may not be explicitly covered within the framework of a guided mentorship. Here we suggest that the graduate school curriculum can play a vital role in teaching and developing these psychosocial competencies through training that involves honing foundational life skills, including students’ motivational-organizational, self-regulation, and social-relational skills. This paper will provide an example of how psychosocial competencies were incorporated into the curriculum at distinct stages of PhD training at one institution.